The E3 ubiquitin ligase CTRIP controls CLOCK levels and PERIOD oscillations in Drosophila. - Lamaze, A.; Lamouroux, A.; Vias, C.; Hung, H.C.; Weber, F.; Rouyer, F. (EMBO Reports, 2011)
In the Drosophila circadian clock, the CLOCK/CYCLE complex activates the period and timeless genes that negatively feedback on CLOCK/CYCLE activity. The 24-h pace of this cycle depends on the stability of the clock proteins. RING-domain E3 ubiquitin ligases have been shown to destabilize PERIOD or TIMELESS. Here we identify a clock function for the circadian trip (ctrip) gene, which encodes a HECT-domain E3 ubiquitin ligase. ctrip expression in the brain is mostly restricted to clock neurons and its downregulation leads to long-period activity rhythms in constant darkness. This altered behaviour is associated with high CLOCK levels and persistence of phosphorylated PERIOD during the subjective day. The control of CLOCK protein levels does not require PERIOD. Thus, CTRIP seems to regulate the pace of the oscillator by controlling the stability of both the activator and the repressor of the feedback loop.